Pengaruh Partisipiasi Anggaran, Budaya Organisasi, Motivasi Kerja Terhadap Kinerja Pengelolaan Keuangan pada Organisasi Perangkat Daerah Kota Semarang - Sujiati Susilaningsih; Sri Sudarsi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of budget participation, organizational culture, and work motivation on the performance of regional financial management in the Regional Apparatus Organizations (OPD) of Semarang City. This study uses a quantitative approach with a survey method. The study population was all 207 OPD employees of Semarang City, with a sample of 136 respondents determined using proportional random sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that budget participation, organizational culture, and work motivation partially and simultaneously have a positive and significant effect on financial management performance. The coefficient of determination value of 82.8% indicates that the independent variables have a strong contribution in explaining variations in financial management performance. This finding emphasizes the importance of employee involvement, strengthening organizational culture, and increasing work motivation in supporting effective and accountable regional financial management.